Pluralisme Agama dalam Tafsir Al-Misbah: Analisis terhadap Pemikiran Quraish Shihab pada Konteks Keindonesiaan - Rezwandi Rezwandi; Ahmad Fikri; Tasya Avanti Digdayani (Jurnal Budi Pekerti Agama Islam, 2025)
This study focuses on examining the concept of religious pluralism as contained in Quraish Shihab's monumental work Tafsir Al-Misbah, with particular emphasis on the significance of his thinking in the contemporary Indonesian landscape. As is widely known, Indonesia is a nation with extraordinary diversity in terms of religion and culture, and it constantly faces the challenge of maintaining social cohesion amid the potential for friction between religious communities. Tafsir Al-Misbah presents a perspective that promotes inclusiveness towards religious pluralism, based on the fundamental universal principles contained in the Qur'an, such as justice, empathy, and respect for diversity. This study implements a qualitative methodology through content analysis techniques on relevant arguments in Tafsir Al-Misbah, particularly those related to interfaith interaction. The results of this study show that: First, Quraish Shihab emphasises the importance of understanding pluralism as sunnatullah (God's decree) and the basis for creating a mutually respectful society. Second, Quraish Shihab's contextual interpretation refers to Indonesia's experience as a multireligious nation.